E-Commerce Penjualan Oli pada King’s Motor Kudus Menggunakan Framework Codeigniter dengan Api Rajaongkir dan Midtrans - Nabilia Nurusyifa; Tri Listyorini; Endang Supriyati (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2023)
This research discusses the process of ordering products online (e-commerce) which will be implemented at KING'S MOTOR KUDUS, a business that sells various kinds of motor oil products and also motorbike service services. By utilizing e-commerce, sellers can offer products online so as to provide convenience for shopping, transactions and shipping effectively and efficiently, consumers do not need to come directly to the store to select the items they want to buy and companies can carry out transaction activities 24 hours a day. In the process of developing this e-commerce website using life cycle development techniques or what can be called a waterfall which includes the stages of System Engineering, Analysis, Design, Coding, Testing and Maintenance. The application was built using the PHP programming language with a database using MySQL and using the CodeIgniter Framework. Consumers can use payment methods through Midtrans. This system uses the method of sending and checking transaction status through the Rajaongkir API. The goal to be achieved from this E-Commerce system is to make it easier for buyers to make transactions wherever the buyer is without having to come directly to KING'S MOTOR KUDUS.